Canada and British Columbia [electronic resource] : copy of all correspondence, from the 1st day of January 1862 to the present time, between the Colonial Office and the Hudson's Bay Company or other parties, relative to a road and telegraph from Canada to British Columbia, and the transfer of the property and rights of the Hudson's Bay Company to other parties. - Hudson's Bay Company.; Great Britain. Colonial Office. ([London? : s.n., 1863)
"Return to an address of the Honourable The House of Commons, dated 10 July 1863; -for." "Ordered, by The House of Commons, to be printed, 15 July 1863." "Colonial Office, 14 July 1863 ." Electronic reproduction. Mode of access: Internet. 44